Muscle-like high-stress dielectric elastomer actuators with oil capsules - La, Thanh-Giang (2014)
Despite being capable of generating large strains, dielectric elastomer actuators (DEAs) are short of strength. Often, they cannot produce enough stress or as much work as that achievable by human elbow muscles. Their maximum actuation capacity is limited by the electrical breakdown of dielectric elastomers. Often, failures of these soft actuators are pre-mature and localized at the weakest spot under high field and high stress. Localized breakdowns, such as electrical arcing, thermal runaway and punctures, could spread to ultimately cause rupture if they were not stopped. This work shows that dielectric oil immersion and self-clearable electrodes nibbed the buds of localized breakdowns from DEAs. Dielectric oil encapsulation in soft-membrane capsules was found to help the DEA sustain an ultra-high electrical breakdown field of 835 MVm-1, which is 46% higher than the electrical breakdown strength of the dry DEA in air at 570 MV m-1. Because of the increased apparent dielectric strength, this oil-capsuled DEA realizes a higher maximum isotonic work density of up to 31.51Jkg-1, which is 43.8% higher than that realized by the DEA in air. Meanwhile, it produces higher maximum isometric stress of up to 1.05 MPa, which is 75% higher than that produced by the DEA in air. Such improved actuator performances are comparable to those achieved by human flexor muscles, which can exert up to 1.2 MPa during elbow flexion. This muscle-like, high-stress dielectric elastomeric actuation is very promising to drive future human-like robots.